Mannose-binding lectin deficiency and miscarriages in rheumatoid arthritis - Juliana Z. Cieslinski; Isabela Goeldner; Thelma l. Skare; Renato Nisihara; Fabiana A. De Andrade; Thirumalaisamy P. Velavan; Iara Messias-Reason; Shirley R. R. Utiyama (Taylor & Francis Group, 2017)
Objective: To investigate the association between mannose-binding lectin (MBL) serum level and MBL2 polymorphisms, and the frequency of spontaneous miscarriages in rheumatoid arthritis (RA) patients. Methods: One hundred seventy seven women (mean age 50 years) with RA from Southern Brazil were studied and 4.5% had a history of abortion (8/177). The MBL levels were determined by ELISA. MBL2 polymorphisms in the promoter (−550H/L, −221X/Y), 5' untranslated region (4 P/Q) and exon 1 (p.Gly54Asp: B allele, p.Arg52Cys: D allele and p.Gly57Glu: C allele; collectively labelled O) were genotyped by sequencing. Results: Mannose-binding lectin levels of RA patients ranged from ≤100 ng/mL to 6640 ng/mL (median 541.5 ng/mL). There was a significant difference in MBL median levels (100 ng/mL vs. 625 ng/mL, respectively, p = .001) and frequency of MBL deficiency (75.0% vs. 24.1%, p = .007, OR = 10.3, 95%CI = 1.9-55.4), in patients with a history of miscarriage vs those without it. Patients with RA and miscarriage had more frequently haplotypes related with low MBL levels (p = .007, OR = 10.5, 95%CI = 1.3-84) than high producers. Moreover, LYPB haplotype and O allele were significantly associated with the occurrence of miscarriage (p = .001, OR = 9.7, 95%CI = 2.4-39.1 and p = .009, OR = 5.9, 95%CI = 1.4-23.4, respectively). Conclusions: The results suggest that MBL deficiency and the presence of MBL2 gene polymorphisms that lead to MBL deficiency are risk factors for the occurrence of miscarriage in patients with RA.